1996
DOI: 10.1177/0011128796042004005
|View full text |Cite
|
Sign up to set email alerts
|

Competing Value Premises for the Provision of Drug Treatment to Probationers

Abstract: Anti-drug-abuse policy debates center on the relative emphasis to be given to prevention, enforcement, and treatment efforts. Even though there are insufficient treatment services to meet the demand, there has been little debate about the question of who should benefit first from the available services. The consequences of lack of such policy for urban probation departments are examined. Lack of an allocation policy appears to be related to unresolved conflicts among competing premises for allocating services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Offenders are often considered lesser citizens 47 and they have diminished civil liberties and responsibilities (i.e., limitations on voting, employment, public housing) 39 . These factors may affect the empathy of general society toward offenders 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Offenders are often considered lesser citizens 47 and they have diminished civil liberties and responsibilities (i.e., limitations on voting, employment, public housing) 39 . These factors may affect the empathy of general society toward offenders 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Table 7 illustrates that prisons are more likely to offer all types of medical, psychosocial, and religious services. In general, fewer services are offered by community correctional agencies, likely because of the assumption that offenders can obtain such services from other organizations in the community, although studies have found that offenders may not always be welcomed by such organizations (Duffee & Carlson, 1996) and that waiting lists often prevent them from gaining access to services.…”
Section: Other Services Provided In Correctional Settingsmentioning
confidence: 99%
“…Of those individuals meeting the criteria of substance use disorders, less than half actually participate in treatment [12]. There are numerous challenges that inhibit individuals from accessing services, including individual motivation for treatment [4,10,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%